CALCULATION METHOD OF DETERMINATION RELIABILITY MEASURES OF HEAT RECOVERY STEAM GENERATOR - M. C. Ankudinova; E. A. Larin; L. A. Sandalova (Известия высших учебных заведений: Проблемы энергетики)
Stochastic calculation model of heat recovery steam generator (HRSG) reliability measures value determination are described in the article. Analysis of metal thermo-stress state of heating surface and analysis of material properties are underlying of method. Failure-free operation is estimated by the non-exceedance condition of working stress over the limit value. Influence of design characteristic of HRSG on failure-free operation is explored in the article. The suggested method is available for parameter optimization of combined cycle gas turbine (CCGT) power plants in Power Supply System and for selecting configuration of CCGT.